Life of a Graduate of Riga Polytechnic Institute Rodrigo Slaviņš, an Engineer and Orienteer, and his Contribution to the Orienteering Sport - Lanka, Ērika; Līcis, Arno (History of Engineering Sciences and Institutions of Higher Education, 2022)
The article reflects on the achievements of Rodrigo Slaviņš, a graduate of the Faculty of Chemistry (1963) of Riga Polytechnic Institute (RPI), an engineer, the Officer of the Order of the Three Stars, three-time champion of the Union of Soviet Socialist Republics (USSR), Master of Sports in orienteering, in the development of orienteering sports traditions, his work at the Latvian Olympic Committee (LOC), as well as his activities as the Head of the Latvian Orienteering Federation (LOF). Special attention is paid to his merit in popularizing orienteering sports and his achievements in competitions of various scales. Developing this article, the authors interviewed R. Slaviņš;. They used his personal archive, the documents of the Latvian National Archives of Latvian State Historical Archive and RTU Archive, the collection of the Latvian National Library, scientific literature, and publications in the press.